Association between exposure to Efavirenz and substrates of dysrhythmia in HIV‐infected young adults. Issue 10 (30th July 2021) - Hosseini, Zahra; Mollazadeh, Reza; Dehghan‐Manshadi, Seyed‐Ali; Mohebi, Mehrnaz; Eslami, Masoud; Sadre‐Bafghi, Seyed‐Ali; Akbari, Ali; Ghodsi, Saeed
Abstract: Background: Dysrhythmia and sudden cardiac arrest occur more likely in HIV patients than healthy subjects. Thus, we need to examine dysrhythmias adverse effects of medications including Efavirenz as early as possible especially in young subjects. Hypothesis: Efavirenz might have contributed to increased risk of developing common types of dysrhythmia in young HIV infected patients. Methods: We performed a retrospective cohort study among 62 patients on Efavirenz and 38 controls. All participants were under 40 years old without cardiovascular disease. Total significant dysrhythmia in 24‐hour ECG monitoring was the primary endpoint determined as the composite of high premature ventricular contraction (PVC) (>500 beats per 24 hours), high premature atrial contraction (PAC) (>500 bp24h ), sinus pause, atrioventricular blocks, ventricular tachycardia, prolonged QTc, and low heart rate variability (HRV). Modified composite dysrhythmia consisted of low HRV (SD of normal‐to‐normal [SDNN]), high PVC and prolonged QT. Results: Mean heart rate, Efavirenz regimen, male gender, and CD4 count predicted total dysrhythmia. Odds ratios were 1.108, 2.90, 4.36, and 0.96, respectively. The incidence of total dysrhythmia, high PVC, high PAC, low HRV(SDNN), and prolonged QTc were 54.8%, 41.85%, 9.71%, 45.2%, and 12.9% in patients on Efavirenz against 42.11%, 31.64%, 0%, 34.2%, and 7.91% in controls, respectively ( p ‐values: .031, .001, <.0001, .063, and .043 respectively). Modified composite dysrhythmia was also more frequent in Efavirenz group than that of control group (69.42% vs. 52.60%, respectively p  = .032). Conclusions: We found that patients with Efavirenz had higher prevalence of frequent PVC, frequent PAC, total significant dysrhythmia, Low HRV and prolonged QTc than controls.